Controle postural em diabéticos tipo 2 com vertigem, tontura e/ou desequilíbrio - Quitschal, Rafaela Maia [UNIFESP] (2018)
Purpose: To evaluate postural control in type 2 diabetics without diabetic polineuropathy, with vertigo, dizziness and/or imbalance. Method: 20 diabetic patients, ranging from 46 to 83 years, of both genders, and a control group of 20 healthy subjects with no complaints paired according to age and gender were submitted to the Brazilian version of the Dizziness Handicap Inventory (DHI), dizziness analog scale, and the Tetrax IBSTM static posturography in eight sensory conditions. Results: The experimental group had moderate impairment in quality of life according to the DHI (mean of 31.30 points) and mean score of 6.45 points in the dizziness analog scale. In all or some sensory conditions, the mean values of the general stability index, frequency bands of postural oscillation, postural oscillation synchronization indexes, and the risk of falling index were significantly higher in type 2 diabetics without neuropathy. Conclusion: Type 2 diabetics with vertigo, dizziness and/or imbalance present postural control impairment, characterized by changes in general stability index, postural oscillation synchronization indexes, frequency bands of postural oscillation and fall risk index.